Resisting representation: Flann O'Brien and Ireland. Issue 4 (2nd April 2020) - Greaney, John
ABSTRACT: This article explores the extent to which Flann O'Brien's early fiction can be read as 'representing' the cultural realities of post-independence Ireland. The rise of the new modernist studies has inspired a host of criticism to explain the Flann O'Brien oeuvre in terms of the cultural dynamics from which it 'emerges'. The early novels, however, given their radically symbolic character – and the particular manner in which they efface memory – are obtuse in relation to (the representation of) Ireland. Through a close reading of their respective narrative modes, it is argued that Ireland is an absent presence which lacks constitutive meaning in At Swim-Two-Birds and The Third Policeman and is thus supplemented by their fictional realities. As such, this article (re)considers the critical criteria for thinking about Irish modernist literature in relation to the history of the nation state.